2019
DOI: 10.1101/691790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural correlates of experience with CCTV surveillance of naturalistic prosocial and antisocial interactions: a reverse correlation analysis

Abstract: 1Previous research using reverse correlation to explore the relationship 2 between brain activity and presented image information found that Face Fusiform 3 Area (FFA) activity could be related to the appearance of faces during free viewing of 4 the Hollywood movie "The Good, the Bad, and the Ugly" (Hasson, et al, 2004). We 5 applied this approach to the naturalistic viewing of unedited footage of city-centre 6 closed-circuit television (CCTV) surveillance. Two 300 second videos were used, one 7 containing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have compared CCTV operators to novices when performing the task of judging harmful intent from CCTV videos. Most studies have found group differences between CCTV operators and novices in brain activity and in the ability to recognize and predict harmful intention (Gillard et al, 2019; Grant & Williams, 2011; Howard et al, 2009; Petrini, McAleer, Neary, Gillard, & Pollick, 2014; but also see Troscianko, Holmes, Stillman, Mirmehdi, Wright, & Wilson, 2004). Hence, studying the differences in information processing between experienced CCTV operators and novices provides a unique window to unveil efficient strategies acquired by human experts through extensive learning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared CCTV operators to novices when performing the task of judging harmful intent from CCTV videos. Most studies have found group differences between CCTV operators and novices in brain activity and in the ability to recognize and predict harmful intention (Gillard et al, 2019; Grant & Williams, 2011; Howard et al, 2009; Petrini, McAleer, Neary, Gillard, & Pollick, 2014; but also see Troscianko, Holmes, Stillman, Mirmehdi, Wright, & Wilson, 2004). Hence, studying the differences in information processing between experienced CCTV operators and novices provides a unique window to unveil efficient strategies acquired by human experts through extensive learning.…”
Section: Introductionmentioning
confidence: 99%